THE ANALYSIS OF MILLENNIAL ENTREPRENEUR’S RESPONSES ON GOVERNMENT FINANCE REGULATION IN MANADO CITY - Sitinjak, Debora C.; Tulung, Joy E.; Pandowo, Merinda H. C. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: Many businesses that continue to grow at this time can help empower MSMEs in Manado city. Hence increasing millennial generation in entrepreneurship will increase the level of acquisition in Manado city. Government has issued government regulation No.46 of 2013, precisely valid starting from July 1, 2013. About tax, in order to facilitate and simplify taxation rules for MSMEs, in this government regulation is calculated from the turnover of each month by 1% and become 0.5% (PP no 23 of 2018). The purpose of this study is to analyse what are the response of millennial entrepreneurs to the government finance regulation. This research is qualitative research by using interview, observation, and using secondary data from media like books, articles, previous researches that support this research. The result show that the attention of the government for millennial entrepreneurs in manado city is important with more socialization about taxation and the awareness of respondent by paying taxes. Recommendation for respondents and the millennial entrepreneurs in Manado city, it should be more orderly in carry out obligations as a taxpayer, so it can help develop MSMEs in Manado city and support the development of the country. Keywords: income tax